The role of organizational commitment in building employee loyalty and its implications for performance - Susanto, Heri; Sofyan, Ade; Mulyasari, Suci (Institute of Computer Science (IOCS), 2025)
This reasearch aimed to identify whether there is a significant relationship between organizational commitment and employee loyalty, and how these two variables affect employee performance. Results from the Pearson correlation coefficient revealed a value of 0.610, which indicates a moderate to strong positive relationship and confirmed that an increase in organizational commitment also contributes to an increase in employee loyalty. From the results of multiple regression analysis, it is found that there then from the results of multiple regression analysis it is also found that there is a strong moderate influence of 44.3% between organizational commitment and loyalty to employee performance